The bicameral system as a successor to decentralisation - Miloš Senčur (Central European Public Administration Review)
The present paper focuses on the issue of territorial principle in a bicameral system which has remained until today the prevailing element in the development of the second chamber of parliament. By presenting its role in the Slovenian and comparable legal systems, the paper suggests that the territorial second chamber of parliament is ever more becoming an indispensable condition also for unitary states with a high level of decentralisation, blurring the distinction between unitary and federal states in such respect. The differences in the role and position of the second chamber are mainly related to the level of decentralisation or development of the local government and, occasionally, to the form of state power. In fact, the weakening of the parliament's role in relation to the executive also diminishes the role and position of the second chamber. Nevertheless, the significance of bicameral decisionmaking in theory and in practice remains unchanged.